2018 IEEE 31st International Symposium on Computer-Based Medical Systems (CBMS) 2018
DOI: 10.1109/cbms.2018.00052
|View full text |Cite
|
Sign up to set email alerts
|

A Portable System for On-Site Medical Spectral Imaging: Pre-Clinical Development and Early Evaluation

Abstract: Imaging is an integral part of most operating room procedures and is used on a daily basis in the operating theater. Near real-time imaging during surgical procedures can significantly enhance the procedures by providing information about the anatomy and pathological conditions. So far, customizable spectral-imaging systems were only rarely investigated, developed and even less often installed in operational settings, especially microsurgery. In this paper we describe a design of portable imaging system for hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…When FN is investigated, the most feasible wavelengths were focused on longer VIS wavelengths, namely, above 644 nm. We did not compare these samples to any other tissues in this study; however, the medium-to-high spectral region has been found most relevant earlier in ex vivo temporal bone and soft tissue studies ( Bartczak et al, 2018 ; Wisotzky et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When FN is investigated, the most feasible wavelengths were focused on longer VIS wavelengths, namely, above 644 nm. We did not compare these samples to any other tissues in this study; however, the medium-to-high spectral region has been found most relevant earlier in ex vivo temporal bone and soft tissue studies ( Bartczak et al, 2018 ; Wisotzky et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a light-absorbing cloth was used to cover the cart to prevent the surrounding light pollution from distorting the measurement. The experimental setup, including image calibration and schematics, has been thoroughly described by Bartczak et al (2018) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation